Characterization of pruriceptive trigeminothalamic tract neurons in rats - Moser, Hannah R. (American Physiological Society, 2014)
Rodent models of facial itch and pain provide a valuable tool for distinguishing between behaviors related to each sensation. In rats, pruritogens applied to the face elicit scratching using the hindlimb while algogens elicit wiping using the forelimb. We wished to determine the role of trigeminothalamic tract (VTT) neurons in carrying information regarding facial itch and pain to the forebrain. We have characterized responses to facially applied pruritogens (serotonin, BAM8–22, chloroquine, histamine, capsaicin, and cowhage) and noxious stimuli in 104 VTT neurons recorded from anesthetized rats. Each VTT neuron had a mechanically sensitive cutaneous receptive field on the ipsilateral face. All pruriceptive VTT neurons also responded to noxious mechanical and/or thermal stimulation. Over half of VTT neurons responsive to noxious stimuli also responded to at least one pruritogen. Each tested pruritogen, with the exception of cowhage, produced an increase in discharge rate in a subset of VTT neurons. The response to each pruritogen was characterized, including maximum discharge rate, response duration, and spike timing dynamics. Pruriceptive VTT neurons were recorded from throughout superficial and deep layers of the spinal trigeminal nucleus and were shown to project via antidromic mapping to the ventroposterior medial nucleus or posterior thalamic nuclei. These results indicate that pruriceptive VTT neurons are a subset of polymodal nociceptive VTT neurons and characterize a system conducive to future experiments regarding the similarities and differences between facial itch and pain.